The role of culture in influencing sexual and reproductive health of pastoral adolescent girls in Karamoja sub-region in Uganda - Stella Achen (SpringerOpen, 2021)
Abstract Sexual and reproductive health (SRH) is vital for general health. However, problems of SRH such as unwanted pregnancies, sexually transmitted infections (STIs), and complications during pregnancy and childbirth among adolescents frequently arise due to risky sexual behaviour. Often, this challenge is linked to socio-cultural issues associated with sexuality which result in disparities in the SRH of adolescent girls. Culture provides rules of sexual conduct between sexes which shape knowledge, beliefs, and practices regarding the sexuality of adolescent girls and influence SRH. However, empirical evidence remains scarce on the role of culture in shaping sexuality which affects the SRH of adolescent girls of pastoral communities. This paper explores the role of culture in shaping the SRH of adolescent girls in the pastoral communities of Karamoja sub-region in Uganda. Using the ethnographic method, qualitative data from interviews, key informants, and focus groups was obtained from adolescent girls, key informants, and old women in Moroto District to understand the perceptions of sexuality. The authors made audio recordings and took field notes. Atlas.ti 8.4.15 was used to organize the data which was analysed using thematic analysis. The findings showed that the perception of wealth defines sexuality and influences SRH, social support for sexual assault victims promotes SRH, and beliefs and practices of sexuality shape the SRH of adolescent girls. Promoting a continuous awareness of the harmful cultural practices is vital in attaining SRH among pastoral adolescent girls. Understanding the role of culture in the influence of SRH is important for the effective provision of SRH services.